Parent and Teacher-Reported Child Outcomes Seven Years After Mild Traumatic Brain Injury: A Nested Case Control Study - Jones, Kelly M.; Starkey, Nicola; Barker-Collo, Suzanne; Ameratunga, Shanthi; Theadom, Alice; Pocock, Katy; Borotkanics, Robert; Feigin, Valery L. (Frontiers in Neurology, 2021)
Background: Increasing evidence suggests potential lifetime effects following mild traumatic brain injury (TBI) in childhood. Few studies have examined medium-term outcomes among hospitalized and non-hospitalized samples. Study aims were to describe children's behavioral and emotional adjustment, executive function (EF), quality of life, and participation at 7-years following mild TBI using parents' and teachers' reports. Methods: Nested case control study of 86 children (68% male, mean age at assessment = 11.27 years; range 7–17 years) who sustained a mild TBI 7-years previously, identified from a prospective, population-based study. They were compared to 69 children free from TBI (61% male, mean age at assessment = 11.12 years; range 5–17 years). In addition to parent-reported socio-demographic details, parents (mild TBI n = 86, non-TBI n = 69) completed age-appropriate standardized questionnaires about children's health-related quality of life, behavioral and emotional adjustment, EF, and social participation. Parents own mood was assessed using the Hospital Anxiety and Depression Scale. Teachers (mild TBI n = 53, non-TBI n = 42) completed questionnaires about children's behavioral and emotional adjustment, and EF. Results: Parent reports showed median group-level scores for cases were statistically significantly greater than controls for emotional symptoms, conduct problems, hyperactivity/inattention, total behavioral difficulties, inhibitory control, shifting, planning/organizing, and Global Executive Composite (total) EF difficulties (p-values 0.001–0.029). Parent reports of child quality of life and social participation were similar, as were teacher reports of child behavioral and emotional adjustment, and EF (p > 0.05). When examining clinical cut-offs, compared to controls, cases had a higher risk of parent-reported total EF difficulties (odds ratio = 3.00) and, to a lesser extent, total behavior problems (odds ratio = 2.51). Conclusions: As a group, children with a history of mild TBI may be at elevated risk for clinically significant everyday EF difficulties in the medium-term compared to non-TBI controls, as judged by their parents. Further multi-informant longitudinal research is required, following larger samples. Aspects requiring particular attention include pre-injury characteristics, such as sleep disturbances and comorbidities (e.g., headaches), that may act as potential confounders influencing the association between mild TBI and child behavioral problems.